Intergration Chracter-Based Curriculum in Character Building of Karuni Christian Junior High School Students - Engel Bertha Halena Gena; I Nyoman Sudiana; Ida Bagus Putra Yasa; Ni Made Rai Wisudarini (Edumaspul: Jurnal Pendidikan, 2024)
The purpose of this research is to identify how the strategic planning through curricular integration in curriculum formation of the students’ character in SMP Kristen Karuni by the curriculum formation and activities programs containing character values. This research applied a qualitative descriptive design to the curricular integration in developing the character values of the students. The result of the research showed that the charactered based curricular integration in SMP Kristen Karuni is effective to develop the students character in the Sriritual and Social aspect, for example; honesty, responsibility, effeciency, indenpendency, and discipline.